0372 Arousability of Insomnia Patients is Not Impacted by the Orexin Antagonist Suvorexant (10 mg and 20 mg). (12th April 2019) - Drake, Christopher L; Cuamatzi-Castelan, Andrea S; Kalmbach, David A; Cheng, Philip; Roth, Thomas; Singh, Meeta; Tran, Michelle K; Tonnu, Christine V; Atkinson, Rachel; Fellman-Couture, Cynthia
Abstract: Introduction: Ability to awaken to external or internal stimuli (arousability) has significant clinical implications in patients with a variety of medical disorders (e.g., sleep related breathing disorders, GERD) and life circumstances (e.g. caregiver responsibility, environmental threat). Arousability with an orexin antagonist has been demonstrated in an animal model. Yet, arousability has not been assessed with orexin antagonists in humans. Thus, we evaluated Auditory Awakening Threshold (AAT) with suvorexant in comparison to placebo. Methods: In a placebo-controlled double-blind 3-way crossover study in 12 (7F) subjects with insomnia, AAT to 1000 Hz tones 2-hrs after bedtime was determined following suvorexant 10 and 20 mg (SUV10, 20) compared to placebo (PBO) administered 30 minutes before bedtime. Tones were presented during stable (5 consecutive minutes) stage 2 sleep in 5db increments starting at 30db. The AAT was compared using one-way repeated measures analysis of variance. Standard sleep parameters of latency to persistent sleep (LPS), wake after sleep onset (WASO), and total sleep time (TST) were also assessed for each condition using paired comparisons. Results: Neither the AAT (expressed as dB) for SUV10 (74.18 ± 23.46) nor SUV20 (83.76 ± 20.24) was significantly different from PBO (79.18 ± 22.34; p = .34). SUV was an active dose in these subjects as seen by significantly greater total sleep time following SUV20 (446.35 ± 23.94 minutes; p = 0.024) compared to placebo (401.09 ± 51.29 minutes). In addition, decreased WASO was observed following SUV20 (22.85 ± 18.50 minutes; p = 0.024) compared to placebo (55.69 ± 40.00 minutes). No significant differences were found for effects of condition on LPS likely reflecting the small sample size. Conclusion: The orexin antagonist suvorexant improved sleep without decreasing nocturnal arousabilty. These results are in contrast to published reports demonstrating blunting of arousal response with benzodiazepine receptor agonists (e.g., zolpidem). Future studies should investigate whether differential arousal response extends into the post-arousal period thereby impacting other behaviors such as ambulating, memory, and cognitive function. Support (If Any): Investigator-initiated grant from Merck Sharp and Dohme Corp.